Working with information as a part of transparency in the activities of prosecutors - Rybalka, Nataliia; Mazuryk, Sviatoslav; Tereshchuk, Halyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article investigates the general provisions of information support of the prosecution of Ukraine in the modern state, characteristics and classification of information in the prosecution activity. It is designed to ensure the author’s definition of information disclosed its features, as well as certain types of information, which operates prosecutor.